MAM - Media Assembly Model - Viel, Caio César (2020)
Video and digital stories are important and empowering contemporaneous means of expression. However, the authorship of digital stories or any audiovisual content, specially when considering multimedia presentation, requires technical knowledge which may hinder the authorship by end-users. The literature presents works that aim to ease the explicit authorship of multimedia presentation by means of declarative languages, frameworks, and tools. Other works propose the implicit authorship using the Ubiquitous Computing paradigm of Capture & Access. The first situation may be not appropriate for highly-interactive application and lacks the features of manipulate individual medias, and the later may not be able to produce the users desired result because of its implicit authorship. In this thesis it is proposed, presented and formalized the Media Assembly Model (MAM) and its companion language, the Media Assembly Language (MAL). Using MAM a user can alter media properties and combine different medias in order to produce new monomedia or create interactive multimedia presentation.